Abraham Ortelius, Hubertus Golzius and Guido Laurinus and the Arx Britannica (Bulletin KNOB, 1999)
Between 1566-1568 the well-known Antwerp map-maker Abraham Ortelius (1527-1598) was involved in the archaeological study of the Arx Britannica, a Roman fortress on the coast of Holland. The ruins were only visible during exceptionally low tide; today the monument has been totally engulfed by the North Sea.The study of the Brittenburg was a group project, probably coordinated by Abraham Ortelius. After Ortelius had drawn a ground plan of the Roman fortress, the painter-numismatist Hubertus Goltzius (1526-1583) sent him an inscription originating from the Brittenburg. The Bruges archaeologist Guido Laurinus (1532-1589) suggested a reconstruction of the inscription, which initiated a reinterpretation of the monument.The participation of Antwerp and Bruges archaeologists in the study of local antiquities in Holland demonstrates that these sixteenth-century humanists did not experience the Northern and Southern Netherlands as separate entities. Possibly Ortelius's interest in the fortress, situated at the Rhine estuary, also had to do with his fascination for antique tribal borders, so characteristic for the outer regions of the former Roman Empire.Eventually the cooperation resulted in the publication of an engraving, in which Ortelius commented on the outcome of the study, presented in a visual form. The engraving was first printed separately, but not really distributed until it was included in the Descrittione di tutti I Paesi Bassi (1581) by L. Guicciardini.The accurate representation of the condition of material sources, such as coins, medals, inscriptions, roof tiles depicted on the engraving is indisputable. Although a new critical attitude towards chronicles is also noticeable, these written sources still had a strong effect.Moreover, the engraving does not show the archaeological discoveries in isolation, but they have been worked into a landscape where ancient Batavians, the so-called lighthouse and sixteenth-century Katwijk exist side by side. Since to Ortelius and his circle object analysis and historicizing sketch were totally compatible, both contributed to a better understanding of the past.